143 Dopamine transporter SPECT imaging: service evaluation from a tertiary neurosciences centre. Issue 12 (14th November 2019) - Kobylecki, Christopher; Harris, Jonathan; Boyle, Mark; Hoffmann, Sandra
Abstract : Background: The use of dopamine transporter SPECT imaging can improve diagnostic accuracy in the assessment of parkinsonism and tremors. In order to manage demand and ensure appropriate use, our tertiary neurosciences centre set up a policy of screening referrals by a movement disorder specialist (C.K.). Objective: To audit the use of [123I]-ioflupane SPECT (DaTscanTM) imaging at Manchester Centre for Clinical Neurosciences. Methods: We audited DaTscan referrals and subsequent results from May 2014-July 2018. The reason for rejection of referrals was documented and subsequent clinical course assessed. We recorded overall indications for imaging and the eventual results. Results: In total, we received 136 referrals for DaTscan, of which 34 (25%) were rejected. Of these, the subsequent course was consistent with the clinical impression in 30 patients for whom follow-up data were available. The most common indications for scans performed were differentiation of Parkinson's disease from tremor syndromes (46%), and suspected drug induced parkinsonism (26%). Equivocal imaging results in 9% were reclassified as normal following quantification. Conclusions: Screening of referrals for DaTscan imaging in a movement disorder service is safe and cost-saving. Appropriate use of DaTscan imaging improves patient management, and equivocal results may be clarified by quantification techniques.